The Role of Notaries in Implementing the Principle of Beneficial Ownership of Corporations in Order to Prevent Crimes of Money Laundering and Terrorism Financing - Wijayanti, Nurlita (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to find out and analyze in depth the implementation of the principle of beneficial ownership by corporations to prevent criminal acts of money laundering and terrorism financing as well as the effects on Notaries and the role of Notaries in Implementing the Principle of Recognizing Beneficial Owners and the role of Notaries in preventing criminal acts of money laundering and terrorism financing. The approach method used by researchers in this thesis is a qualitative approach method. The type of research used by the author in his thesis is empirical legal research. Types and Sources of Data used are primary data sources and secondary data sources. Data collection methods are descriptive, namely interviews and observations. Data Analysis Method The research conducted by the author is descriptive. The results of the research and discussion show that: First, the government's implementation of corporate transparency is by uncovering the principle of beneficial ownership by blocking corporate access to OSS and SABH so that corporations will have difficulty in running their business so that the Notary is the party who has the authority to unblock the block. Second, the role played by a Notary means something that is carried out related to the Notary's duties or obligations in carrying out his work. The role of the Notary in preventing TTPU and Terrorist Financing by revealing beneficial owners in order to minimize the establishment of corporations that aim to commit these crimes by obtaining information regarding beneficial owners, Submitting information related to beneficial owners, Arranging documents related to beneficial owners.